2018
DOI: 10.1007/s10511-018-9533-x
|View full text |Cite
|
Sign up to set email alerts
|

Light Chemical Elements in Stars: Mysteries and Unsolved Problems

Abstract: them were initially synthesized in the Big Bang. The primordial abundances of these elements calculated using the Standard Model of the Big Bang (SMBB) are presented in this review. The good agreement between the SMBB and observations of the primordial abundances of the isotopes of hydrogen and helium, D, 3 He, and 4 He, is noted, but there is a difference of ~0.5 dex for lithium (the isotope 7 Li) between the SMBB and observations of old stars in the galactic halo that has not yet been explained. The abundanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…As an example of good agreement with these results, one may indicate an analysis of the N/O ratio for 46 early B-type MS stars (Lyubimkov 2016(Lyubimkov , 2018. It was found that most of the stars near the MS termination (82 %) show the relatively low values [N/O] < = 0.3; from the viewpoint of the theory (Georgy et al 2013), these stars had the low initial rotational velocities V 0 from 0 to 130 km/s.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…As an example of good agreement with these results, one may indicate an analysis of the N/O ratio for 46 early B-type MS stars (Lyubimkov 2016(Lyubimkov , 2018. It was found that most of the stars near the MS termination (82 %) show the relatively low values [N/O] < = 0.3; from the viewpoint of the theory (Georgy et al 2013), these stars had the low initial rotational velocities V 0 from 0 to 130 km/s.…”
Section: Discussionmentioning
confidence: 60%
“…Nevertheless, it should be stated that such accordance between observations and the theory exists not always. As noted in Lyubimkov (2018) review, there is a significant discrepancy between observations and the theory for helium, the main product of CNO-cycle. The same computations of Georgy et al (2013), which seem to be successful in the case of C, N and O, cannot explain the observed helium enrichment in the B-type MS stars.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The first of these two problems concerning giants and supergiants that are rich and super-rich in lithium has been discussed in some detail in a review [2]; some details on light elements are also given in Ref. 3. As noted there [2,3], most lithium-rich stars and all stars that are super-rich in lithium cannot be explained in terms of the standard theory of stellar evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The standard Big Bang nucleosynthesis (BBN) theory is not effective to explain the generation of 6 Li, 9 Be, 10 B, 11 B [27-29], what is reflected in the low abundance of these simple species. Recently, according to [30], there are modern data indicating that first chemical elements up to oxygen are formed in Big Bang nucleosynthesis. Nevertheless, the abundance questions are among unsolved problems.…”
Section: Introductionmentioning
confidence: 99%